2010
DOI: 10.3851/imp1516
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin therapy for patients with idiopathic cardiomyopathy and endomyocardial biopsy-proven high PVB19 viral load

Abstract: The present pilot study demonstrates that IVIg significantly reduces viral load and improves cardiac function in patients with DCM related to increased PVB19 viral load in the heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 54 publications
0
65
0
13
Order By: Relevance
“…Unpublished experience 111 found benefit with cytomegalovirus hyperimmune globulin with cytomegalovirus myocarditis, and a recent study 115 found benefit of high-dose IVIG therapy in patients with idiopathic cardiomyopathy and high parvovirus B19 myocardial load. Immunoadsorption of anti-cardiac antibodies, although not clinically available universally, has been associated with improvement in left ventricular function in inflammatory cardiomyopathy in a single-center experience.…”
Section: Diagnosis and Therapy For Myocarditis In Children 121mentioning
confidence: 99%
“…Unpublished experience 111 found benefit with cytomegalovirus hyperimmune globulin with cytomegalovirus myocarditis, and a recent study 115 found benefit of high-dose IVIG therapy in patients with idiopathic cardiomyopathy and high parvovirus B19 myocardial load. Immunoadsorption of anti-cardiac antibodies, although not clinically available universally, has been associated with improvement in left ventricular function in inflammatory cardiomyopathy in a single-center experience.…”
Section: Diagnosis and Therapy For Myocarditis In Children 121mentioning
confidence: 99%
“…These findings suggest differences in pathophysiologic mechanisms between DCM in IMID patients and virusinduced forms of DCM. This may be important, since treatment strategies for the two forms of DCM may differ (12,16,21).…”
Section: Discussionmentioning
confidence: 99%
“…DNAs or RNAs of parvovirus B19, human herpesvirus 6, adenovirus, Epstein-Barr virus, and enterovirus were identified and quantified with quantitative PCR as described previously (12). DNA was extracted from endomyocardial biopsy specimens using a QIAamp DNA blood minikit (Qiagen, Venlo, Netherlands).…”
Section: Study Population (I) Dcm Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apesar de baixa incidência, a evolução para óbito ou transplante cardíaco é elevada nesta entidade, especialmente quando não realizada imunossupressão 280 ; além disso, existe risco de recorrência fatal com a suspensão da imunossupressão. Na miocardiopatia dilatada idiopática (sintomas de IC acima de um ano), de maneira pioneira, estudo holandês utilizando técnica de biologia molecular quantitativa (PCR Real Time) demonstrou melhora da função ventricular em pacientes tratados com imunoglobulina que apresentavam títulos elevados de genoma viral de parvovírus B19 no tecido miocárdico 281 .…”
Section: Miocardite (Tabela 35)unclassified